(untitled) (Medical Forum Monthly, 2022)
Objective: The purpose of this study was to compare the oncological outcomes of oncologic breast surgery and the conventional breast conservative surgery in the patients with early breast carcinoma. Study Design: A retrospective study Place and Duration of Study: This study was conducted at the Surgical Department of Khalifa Gul Nawaz Teaching Hospital Bannu from January 2014 to January 2017 in collaboration with BINOR (Bannu Institute of Nuclear Medicine Oncology and Radiotherapy) and was compiled in August 2021. Materials and Methods: A total of 220 patients (all females) with early breast carcinoma (T1, T2, N0, N1 & M0) with the age ranged from 26-85 years with the mean age 47 years were included in this retrospective study. Results: Out of the 220 patients with early breast carcinoma (T1= 90, T2= 130 patients), 160 patients were treated by Modified radical mastectomy (MRM) and 60 patients subjected to Breast conservative therapy/surgery (BCS). After a follow up period of 5 years, there were no significant differences in the overall survival (86.7% vs. 88%, p= 0.62), disease free survival (67% vs. 70%, p= 0. 63) or the mortality (13.3% vs. 11.8%, p= 0.61) of patients treated with breast conservative surgery (BCS) or modified radical mastectomy (MRM) However, there was a significant difference in the rate of local recurrences (32.7% vs. 16.3%, p= 0. 001) of patients treated with BCS or MRM. Conclusion: BCS is a suitable/standard alternative for MRM in selected cases of early carcinoma breast, with comparable overall survival, disease free survival and mortality rates in BCS and MRM. BCS was associated with increased local recurrences. BCS maintains the quality of life and have a good cosmetic value.